Peningkatan Menulis Teks Anekdot Menggunakan Model Problem Based Learning Siswa Kelas X IPA 1 MA Manongkoki Kab. Takalar (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
The purpose of this study was to improve students' ability to write anecdotal texts using the Problem Based Learning model in class X IPA 1 MA Manongkoki Kab. Takalar. This type of research is class action research (Class Action Research) and consists of two cycles, with two cycles carried out in two sessions. Research methods include planning, implementation, action, observation and reflection. The research was conducted at MA Manongkoki, Kab. Takalar. The target of this study were 23 students of class X IPA 1 MA Manongkoki District. Studies show that the average increases from 67.47% in the first period to 84.43% in the second period. Based on the results of the research above, it can be concluded that the Problem Based Learning model increases in learning to write anecdotal texts.